Analisis pengaruh pertumbuhan ekonomi dan tingkat inflasi terhadap pengangguran perbuka di Provinsi Jambi pendekatan vector error correction model (VECM) - Podi, Syafitri Inten; Zulfanetti, Zulfanetti; Nurhayani, Nurhayani (Jurnal Paradigma Ekonomika, 2020)
The purpose of this study is to determine the development of the level of open unemployment, economic growth, and inflation in Jambi Province and to determine the effect of economic growth and inflation on open unemployment in Jambi Province in the short and long term. This research uses secondary data. This study uses a quantitative descriptive approach with a Vector Error Correction Model (VECM). The results of the data analysis show that the level of open unemployment, growth, and inflation has fluctuated figures. In the short term, none of the variables has a significant effect on the level of open unemployment. Economic growth on the open unemployment rate in 2000-2017 in the short run has a positive and insignificant impact, while inflation on the open unemployment rate in 2000-2017 in the short run has a negative and insignificant impact. The effect of economic growth on the open unemployment rate, in the long run, has a positive and significant impact, meaning that if there is an increase in economic growth it will increase the level of open unemployment in the long term. The effect of inflation on the open unemployment rate, in the long run, has a negative and insignificant impact.